Parameter extraction and modelling of the MOS transistor by an equivalent resistance. Issue 1 (2nd January 2021) - Sharroush, Sherif M.; Abdalla, Yasser S.
ABSTRACT: During the analysis of multi-transistor circuits, the need arises to evaluate the time delay or the power consumption of the circuit. Due to the complexity of the transistor model, several complicated equations arise from which a compact-form solution cannot be obtained and a suitable physical insight cannot be drawn. With this regard, two contributions are presented in this paper. The first one is a fully analytical parameter extraction approach to be applied on the MOS transistors. The second one is a quantitative method for simplifying the analysis of MOS circuits by modelling the MOS transistor by a suitable equivalent resistance adopting the time-delay or the power-consumption equivalence criteria. The parameter-extraction method is verified by using the extracted parameters in the derived expressions according to the second contribution. Compared to other representations, the agreement of the proposed model with the simulation results is very good.